Pulmonary histiocytic sarcoma in a rabbit. (2nd August 2013) - Leissinger, Mary; Brandão, João; Wakamatsu, Nobuko; Le, Alexandre; Rich, Gregory; Gaunt, Stephen
Abstract An approximately 8‐year‐old male castrated Dutch rabbit was evaluated for a 6‐day history of respiratory signs, which began as sneezing and progressed to tachypnea with anorexia. On physical examination, tachypnea and pale mucous membranes were noted. Thoracic radiographs revealed a soft tissue pulmonary mass, fine‐needle aspirates of which confirmed a neoplasia with malignant features suspicious for a histiocytic sarcoma. The rabbit was discharged and due to a rapidly deteriorating condition, the owner declined chemotherapy with Lomustine and elected euthanasia of the rabbit. The affected lung was submitted for histopathology. Histologic sections of the lung were characterized by clusters of histiocytic cells and multinucleated giant cells with occasional invasion of blood and lymphatic vessels. The histologic diagnosis was histiocytic sarcoma. To the authors' knowledge, this is the first case report of histiocytic sarcoma in a rabbit. Based on the clinical and radiologic findings in this case, histiocytic sarcoma should be included in the list of differentials for rabbits presenting with respiratory signs and evidence of a pulmonary mass.